2014
DOI: 10.1016/j.ijsu.2014.08.398
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of bronchiectasis: A retrospective observational study of 260 patients

Abstract: Surgery is an effective treatment option for bronchiectasis. Sputum volumes lower than 30 mL, negative proof of Gram-negative bacteria and bronchial stump coverage using intercostals muscles or pedicle pleura embedding are the key factors for successful treatment. Special attention has to be given to any complications in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
1
16
0
5
Order By: Relevance
“…In this study, the mean age of patients was 49.06 years old, which was younger than the average age in other large-sample reports. However, some studies on surgical treatment of bronchiectasis reported that the median age of these patients was less than 50 years old (31,32). This may be explained by that older patients are more likely accompanied by comorbidities and therefore be less eligible for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean age of patients was 49.06 years old, which was younger than the average age in other large-sample reports. However, some studies on surgical treatment of bronchiectasis reported that the median age of these patients was less than 50 years old (31,32). This may be explained by that older patients are more likely accompanied by comorbidities and therefore be less eligible for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with bronchiectasis typically presented with signs of recurrent infections, productive cough, and hemoptysis. 11,23 Our study showed significant symptomatic improvements after lobectomy for the predominant lesion in nonlocalized bronchiectasis. The frequency of acute infection and hemoptysis declined significantly and the amount of sputum decreased.…”
Section: Discussionmentioning
confidence: 59%
“…Details of patient preoperative evaluation have been reported in previous publications. 3,4,11 To summarize, thoracic CT was performed to locate the predominant lesion. The extent of bronchiectatic lesions that was expected to be left behind was expressed as a proportion of the remaining lungs, which was calculated by the anatomic method, where the total number of segments for both lungs was deemed 19 (10 in the right lung and 9 in the left lung).…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Therapieversagen der konservativen Behandlung Das festgestellte Versagen der medikamentösen, nicht operativen Therapie wird heutzutage als Indikation zur Operation resektabler Bronchiektasen angesehen und allgemein akzeptiert [1,3,18,22,29,50] (s. a. Infobox "Indikationen"). Üblicherweise wird Therapieversagen hierbei definiert als entweder häufige Exazerbationen mit signifikanter Beeinträchtigung des sozialen und beruflichen Lebens oder als Notwendigkeit multipler Hospitalisationen innerhalb kurzer Zeitabstände trotz Ausschöpfung der zur Verfügung stehenden nichtoperativen Behandlungsverfahren [18].…”
Section: Indikationen Zur Lungenresektionunclassified
“…In aktuellen chirurgischen Fallserien leiden die Patienten daher an einer Vielzahl von durch Bronchiektasen bedingten Beschwerden, die durch die konservative Therapie nicht mehr zur Abheilung gebracht werden können. Im Vordergrund stehen [1,3,16,18,22,29]: " rezidivierende bronchopulmonale Infektionen (50 -90 %), " produktiver Husten (20 -90 %), " eitriges Sputum (15 -80 %), " Thoraxschmerz (5 -10 %), " Gewichtsverlust (5%) sowie " Fieber und Nachtschweiß (3 %).…”
Section: Indikationen Zur Lungenresektionunclassified